MEDICOLEGAL STUDY FOR DETERMINING THE PRESENCE OF SEMEN BY USING HISTO - CHEMICAL COLOR REACTION (Journal of Forensic Medicine & Toxicology, 2018)
It is very helpful in clarifying the facts of crimes to find and examine the forensic evidence materials through the medicolegal examination. We investigated for determining the presence of semen in the putrefaction of semen, oldness, mixing with other materials, and aspermia and so on, and then some issues related with our study were covered in this article.